PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP KETERAMPILAN MENULIS PUISI DI KELAS V SEKOLAH DASAR NEGERI 21 PONTIANAK BARAT - Arista, Prilly; Kaswari, Kaswari; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study is to describe the influence of Indonesian language learning to apply audio visual media to the skills of writing poetry in class V Elementary School Negeri 21 Pontianak Barat. This research uses experimental experimental type experiment with design time series design design. The population in this research is all students of class V of Elementary School of Negeri 21 Pontianak Barat which consists of three classes. The sample of this study is the VC class of 23 students. Instruments in the form of test with the form of acquisition of results as much as 1 problem. Data collection techniques use measurement techniques. The result of hypothesis test using t-test (t test dependent) obtained t_ (count) of 4.607 for dk 23 and Î± = 5% obtained t_ (table) of 1.717, which means t_hitung> t_table (4,016> 1,717), from the calculation effect size (ES), an average of 0.29 was obtained. So, it can be concluded that there is influence of audio visual media to poetry writing skill in class V Elementary School Negeri 21 Pontianak BaratÂ Keywords: Influence, Audio Visual Media, Poetry Writting Skill.